The Problems and Solutions of Thailand students’ Arabic Speaking Skills at Darussalam Modern Islamic Boarding School: مشكلات طالبات تايلاند في مهارة الكلام العربي وحلها بالمعهد الإسلامي في إندونيسا - Zaid, Abdul Hafidz bin; Fakhiroh, Alinda Zakiyatul; Sonia, Eva; Layalia, Nada Ni'ma; Nor, Azhar (Institut Agama Islam Negeri Palangka Raya, 2022)
This research is based on the students’ decreasing score in Arabic speaking test, especially the foreign students from Thailand in every batch year. This research is aimed to know the problems of Thailand students in Arabic speaking skills and to know the right solution which can help them answer exam questions. This research used qualitative method by collecting data with triangulation model. The result of this research showed that the problems of Thailand students in Arabic speaking skills were the lack of formal language exposure among the students so that they felt difficult to learn or understand Arabic, the strict regulations of using Arabic make them feel constrained so they are reluctant to speak Arabic, and the lack of confidence in speaking Arabic. As for the solution of these problems were giving them more Arabic vocabulary and motivation them in speaking Arabic, evaluating the language, and encouraging them to increase their interactions with other students apart from their Thailand fellow students so that they get used to speak in Arabic. It is suggested to conduct further research by investigating the influence of these solutions for Thailand students in speaking Arabic.